2004
DOI: 10.1021/jm030580l
|View full text |Cite
|
Sign up to set email alerts
|

The PDBbind Database:  Collection of Binding Affinities for Protein−Ligand Complexes with Known Three-Dimensional Structures

Abstract: We have screened the entire Protein Data Bank (Release No. 103, January 2003) and identified 5671 protein-ligand complexes out of 19 621 experimental structures. A systematic examination of the primary references of these entries has led to a collection of binding affinity data (K(d), K(i), and IC(50)) for a total of 1359 complexes. The outcomes of this project have been organized into a Web-accessible database named the PDBbind database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
901
3
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 866 publications
(909 citation statements)
references
References 26 publications
(37 reference statements)
2
901
3
3
Order By: Relevance
“…Second, inhibitors of PARP and PTP were taken from the results of a combination of both virtual and high-throughput screening [26,27]. Third, the PDBbind database [28] was used to generate a large number of additional cases for testing screening utility. From the full 800 complex set, all proteins were identified that were represented with at least five different ligands.…”
Section: Pham Screening Enrichment Setmentioning
confidence: 99%
“…Second, inhibitors of PARP and PTP were taken from the results of a combination of both virtual and high-throughput screening [26,27]. Third, the PDBbind database [28] was used to generate a large number of additional cases for testing screening utility. From the full 800 complex set, all proteins were identified that were represented with at least five different ligands.…”
Section: Pham Screening Enrichment Setmentioning
confidence: 99%
“…The majority of cellular adhesion molecules bind with energies near 10kT, making the individual bonds reversible. [65][66][67] Also worth mentioning is the importance of the binding kinetics. Binding and unbinding rate constants comprise a "state space" in which different families of adhesion molecules reside and accomplish their function.…”
Section: Introductionmentioning
confidence: 99%
“…Since the QSAR score was originally trained by kinaseinhibitor dissociation constant, an indirect indicator of kinase (Liu et al, 2007) and PDBbind (Wang et al, 2004) databases.…”
Section: Virtual Screening Of Rho Inhibitor Candidatesmentioning
confidence: 99%